A Rare Case Of CNS High-Grade Neuroepithelial Tumor With BCOR Alteration (HGNET-BCOR). (28th October 2020) - Al-Habib, A; Bhattacharjee, M
Abstract: Introduction/Objective: HGNET-BCOR is a distinct molecular CNS tumor entity that was first identified by DNA methylation analysis in 2016. It is defined by an in-frame internal tandem duplication in exon 15 of the BCOR gene. The BCOR mutation is not unique to this tumor entity and can be seen in other CNS tumors, as well as solid organ and hematologic malignancies. In this report, we describe the pathology in a 2-year-old girl with a posterior fossa brain tumor initially diagnosed as high-grade neuropeithelial tumor at an outside facility. Methods: She underwent resection and adjuvant chemotherapy at the same institution. She presented later to our hospital complaining of fatigue and vomiting, and tumor recurrence on MRI. Microscopic examination of the recurrent tumor showed a relatively circumscribed lesion with atrophic cerebellar folia associated with some of the tumor fragments. Tumor cells were arranged in papillary, pseudopapillary, and rosetted patterns in a myxoid (Alcian-blue positive) background. The tumor showed regional necrosis and frequent mitoses (mitotic index 14–15 /10 HPFs). An extensive panel of immunostains was performed. Results: The tumor was diffusely and strongly positive only for vimentin and EGFR, with diffuse moderate staining for BCL-2, and patchy weak staining for S100 protein. There were rare, focal tumor cells with GFAP and neurofilament staining. The Ki67 labeling index was 80–90%. All other tested markers were negative. The primary tumor resection was later found to be positive for BCOR by IHC. Sequencing for exon 15 of the BCOR gene showed an in-frame internal tandem duplication. Conclusion: These features are consistent with the diagnosis of HGNET-BCOR. The pathologic and clinical features for this rare tumor entity are not widely known. Further studies with additional patients are needed to expand our understanding of these rare tumors to develop new treatment approaches.